IoT-based Facelook and Fingerprint Safe Security System - Josya Marvin Immanuel; Ibrahim Ibrahim; Reni Rahmadewi; Yuliarman Saragih (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop an advanced safe security system by combining Facelook and Fingerprint technologies based on the Internet of Things (IoT). These technologies are expected to provide a higher level of security and facilitate access for safe owners. Subsequently, testing is carried out on the safe's opening mechanism after successful authentication via both the fingerprint sensor and the face recognition system. These trials encompass the evaluation of success rates, the speed of the opening mechanism, and the overall response time. Data from the testing phase is collected and analyzed to comprehensively assess the system's performance. The average notification delivery delay for the face recognition system was measured at 2.67 seconds with a standard deviation of 0.37. The notification delivery data revealed an average delay of 2.04 seconds with a standard deviation of 0.38 These findings collectively affirm the effectiveness of the integrated face recognition and fingerprint system in the proposed safe security setup